Kajian Etika Kebajikan dan Prinsip Universalisme Islam dalam Pelayanan Rumah Sakit (Studi Kasus Rumah Sakit Umum Hartati Medical Centre, Rantauprapat, Sumatera Utara) - Irwansyah Putra; Lucky Nugroho; Zulfahmi (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2024)
The aim of this research article is to determine the trend of non-Muslim patients and the level of service satisfaction for registration officers at RSU HMC, Rantaprapat. The problem formulation in this research includes (i) How many non-Muslim patients are there at HMC General Hospital during 2021 to 2023? (ii) How does the registration officer provide services to non-Muslim patients? The research methods used. Next, a quantitative method using secondary data to collect information regarding the number of patients and using a questionnaire to measure satisfaction of non-Muslim patients. The results of this study show that the number of non-Muslim patients has increased. In addition, the results of the questionnaire show that the overall service of registration officers at RSU HMC is 85%, which means that the majority of non-Muslim patients are satisfied with the service. This research also provides practical implications that can be directly applied by hospital management to improve service quality and internal policies. The novelty of this research relates to experiences and attitudes towards non-Muslim patients which have not been studied much before.